THE CREDIT CHANNEL TRANSMISSION OF MONETARY POLICY IN TUNISIA - MNA, Ali; YOUNSI, Moheddine (Theoretical and Practical Research in Economic Fields, 2018)
The purpose of this paper is to evaluate the importance of the credit channel in the monetary policy transmission mechanism in Tunisia . Using a VAR approach, we attempt to empirically examine the responses of the major aggregates of the Tunisian economy to monetary policy shocks over the period 1965-2015. Our empirical results show that credit has a significant effect on investment and inflation. The cointegration relationship coupled with the weak erogeneity test shows that credit is an endogenous variable and therefore the long-term equation found is a credit equation. The crucial role of credit channel is argued by the goal of price stability expected by any monetary policy. The analysis of monetary shocks shows the importance of exchange rate policy and the local currency devaluation on the financing mode. It is seen that Tunisian economy is dominated by external conditions. This dominance is confirmed by extensive using of external debts and trade agreements with the dominant countries. The main findings suggest that policymakers should act on the level of economic activity and inflation, on two terms. The first is in short-term by acting on the interest rate and the second is in long-term by controlling the exchange rate.